2007
DOI: 10.1163/157361107781360040
|View full text |Cite
|
Sign up to set email alerts
|

Elastoviscoplastic Model and Concept of Slip

Abstract: The model of elastoviscoplastic medium is based on the concept of slip proposed by Batdorf and Budiansky. The conditions of slip on a slip plane take into account the dependence of tangential stresses on slip velocity. But when the viscosity is low, they are almost similar to the dry friction conditions. Under some assumptions we succeeded in integrating the plastic shear rates over all possible slip planes in case of arbitrary three‐dimensional stress state and obtained an expression for the plastic strain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In [8] is shown, that in the approximation under consideration 13 1 S ε = + , 1 ε << at the contour the values of the integration limits over ϑ can be depicted as:…”
Section: The Integration and Its Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [8] is shown, that in the approximation under consideration 13 1 S ε = + , 1 ε << at the contour the values of the integration limits over ϑ can be depicted as:…”
Section: The Integration and Its Resultsmentioning
confidence: 99%
“…Let's consider them individually. τ − > This condition is thoroughly investigated in [8]. As a result it was obtained that the integration limits over ϑ are given by:…”
Section: The Plastic Strain Tensormentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that yield–stress fluids exhibit wall slip, leading to dispersion phenomena adjacent to the walls (Barnes, 1995; Nikitin, 2007; Ballesta et al. , 2012; Damianou and Georgiou, 2014; Jing et al.…”
Section: Introductionmentioning
confidence: 99%